Unlocking the mystery of the role of Vitamin D in iron deficiency anemia in antenatal women: a case control study in a tertiary care hospital in New Delhi - Tanishq Hitesh; Ritu Khatuja; Poonam Agrawal; Deepak Dhamnetiya; Ravi Prakash Jha; Prachi Renjhen (BMC, 2023)
Abstract Background Vitamin D deficiency and anemia are clinical conditions that coexist during pregnancy. A high prevalence of Vitamin D deficiency ranging from 50 to 94% is seen throughout the country. The aim of the study was to discover the association between Vitamin D status and iron deficiency anemia during pregnancy. Improving the vitamin D status of pregnant women is crucial to prevent iron deficiency anemia and can improve maternal and fetal outcomes. Methods A case-control study including 94 primigravida women of age within the age group 18 to 30 years, divided into two groups: a Case Group of 48 patients with already diagnosed iron deficiency anemia (mild to moderate) and a Control Group of 46 antenatal women with normal hemoglobin levels. Data on sociodemographic, clinical characteristics, and the levels of 25(OH) Vitamin D was estimated in both the groups. The association of 25(OH)D levels and anemia was then determined using suitable statistical analysis. Results Among pregnant women affected with anemia, 75% of women had serum Vitamin D concentrations < 20 ng/ml compared to 52.2% of women in the controls. Maternal serum vitamin D level was significantly lower in pregnant women affected with anemia (19.61 ± 13.12) as compared to control (29.43 ± 24.05); (p = 0.024). A positive correlation was found between hemoglobin and vitamin D levels in pregnant women (Pearson's r = 0.200, p = 0.05). Conclusions These findings provide evidence suggesting that Vitamin D deficiency or insufficiency during pregnancy may be a risk factor for anemia and correction of Vitamin D levels can improve hemoglobin levels. Educational efforts should be made to include safe vitamin D intake in antenatal care.